Asymptotic expansions for steady periodic water waves in flows with constant vorticity. (October 2017) - Kalimeris, K.
Abstract: We provide high-order approximations to periodic travelling wave profiles, through a novel expansion which incorporates the variation of the total mechanical energy of the water wave. We show that these approximations are extended to any finite order. Moreover, we provide the velocity field and the pressure beneath the waves, in flows with constant vorticity over a flat bed.